Plan de Negocios, mediante el Estudio de Mercado, para proponer la creación del Complejo Turístico, “BRISAS DEL PAYAMINO”, en el Cantón Francisco de Orellana - Carrillo Ordoñez, Enma Lucia (2018)
The province of Orellana is one of the regions belonging to the Ecuadorian East, and its capital Francisco de Orellana is considered as a fascinating site of Ecuador, Heir of millenary cultures and a rich colonial tradition, constituting a magical sector that houses one of the most greater biodiversities of the planet and a true melting pot of different indigenous cultures, so few regions can offer so many landscapes and virgin forests, the diversity of its flora and fauna and the hospitality of its inhabitants make up the enormous potential to develop the tourism industry in Canton Francisco de Orellana. Tourism destinations are in exploitation processes and it is the objective that they are known throughout the world. However, many attractions of the canton Francisco de Orellana, until recently little exploited, are being more demanded by tourists, boosting other regions and segments of the tourism sector. The fundamental objeitvo of the Investigation is about conducting a market study to propose the creation of a tourist complex in the canton Francisco de Orellana, which will allow to determine whether or not there is the necessary demand for its implementation. The materials that were used were useful office, office equipment, among others, as well as the different methods: analytical, descriptive, explanatory and statistical analysis, which allowed to go makinnalysis in each of the phases of the investigation. The project investment amounts to $ 396,899.52, of which 24% is financed by the partners and 76% with a loan to the National Financial Corporation, at 11.85% for a 10-year term. The Financial Evaluation determines that the project is feasible since the analysis of the indicators are positive, such as: LA TIR with 27.21% higher than the opportunity cost; the NPV, which is $ 400,764.45, higher than the investment, the Benefit Cost Ratio which is $ 1.30 of profitability for each dollar invested, the period of recovery of capital, which is 4 years, 2 months, 5 sixteen days and the sensitivity analysis that supports an increase in costs of 58.60% and a decrease in income of 26.60%, therefore the project is not sensitive and therefore can be executed. Therefore, when obtaining favorable results, it is pertinent to motivate the investors to execute the project, considering the benefits that will bring to those who invest in them and for the socioeconomic development of the parish the canton, the province and therefore the country.